Radionuclide Release Prediction in Water and Soil at Demonstration Plant of Near Surface Disposal for Radioactive Waste - Pandu Dewanto; Setyo Sarwanto Moersidik; Sucipta Sucipta (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2016)
Near Surface Disposal (NSD) for Radioactive Waste that should be developed due to increment of the low level radioactive waste, need to be analyzed and evaluated related to the radiological impact of the environment. A research method applied is done by modeling the distribution of radionuclide releases process. Analysis related with the releases of radionuclide in water and soil is using PRESTO (Prediction of Radiological Effects Due to Shallow Trench Operations). The application scenarios selected in this safety assessment is the migrations of Co-60 and Cs-137 scenario through the shallow groundwater flow pattern in the NSD site. The SigmaPlot software is also used to determine the concentration equation in well water and river water. The final results showed the concentration of radionuclide in wells and streams below the provision. Radionuclide activity concentrations in well ranged from 10-10Bq/m3 to 100Bq/m3 and in the river ranged from 10-15Bq / m3 to 10-1Bq / m3. The impact of radioactive waste of radionuclide Co-60 and Cs-137 will decrease to the background radiation level at a distance less than 10m and penetrate into the saturated layer up to 4m. In this study, an equation have been obtained that can predict radionuclide concentration patterns based on the distance and the depth of the ground surface against to the facility operation time.